2021
DOI: 10.1155/2021/1989917
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of ZBTB16 as a Prognostic Marker for Ewing’s Sarcoma

Abstract: Objective. The purpose of this study is to identify novel biomarkers for the prognosis of Ewing’s sarcoma based on bioinformatics analysis. Methods. The GSE63157 and GSE17679 datasets contain patient and healthy control microarray data that were downloaded from the Gene Expression Omnibus (GEO) database and analyzed through R language software to obtain differentially expressed genes (DEGs). Firstly, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment, protein-protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…We also found that several non-cancer related pathways including citrate cycle, dilated cardiomyopathy, cardiac muscle contraction and focal adhesion were enriched in KEGG analysis. Interestingly, many of these pathways such as dilated cardiomyopathy and cardiac muscle contraction, have also been discovered to be related to ES progress in a recent study (Ding et al 2021). Finally, GSEA analysis showed 25 significantly activated and 7 suppressed pathways (Fig.…”
Section: Identification Of Enriched Pathways In Esmentioning
confidence: 78%
“…We also found that several non-cancer related pathways including citrate cycle, dilated cardiomyopathy, cardiac muscle contraction and focal adhesion were enriched in KEGG analysis. Interestingly, many of these pathways such as dilated cardiomyopathy and cardiac muscle contraction, have also been discovered to be related to ES progress in a recent study (Ding et al 2021). Finally, GSEA analysis showed 25 significantly activated and 7 suppressed pathways (Fig.…”
Section: Identification Of Enriched Pathways In Esmentioning
confidence: 78%
“…We used the cytoHubba application in Cytoscape software to build a PPI network. The Cytoscape Molecular Complex Detection (MCODE) plug-in was used to select the most closely connected module from the existing PPI network, and we set the filter conditions as degree cutoff = 2 to carry out further functional analysis [ 20 ].…”
Section: Methodsmentioning
confidence: 99%